Charge-transfer complexes based on C2v-symmetric benzo[ghi]perylene: comparison of their dynamic and electronic properties with those of D6h-symmetric coronene. (24th April 2018) - Yoshida, Yukihiro; Tango, Shunsuke; Isomura, Kazuhide; Nakamura, Yuto; Kishida, Hideo; Koretsune, Takashi; Sakata, Masafumi; Nakano, Yoshiaki; Yamochi, Hideki; Saito, Gunzi
Abstract : Dynamic and electronic properties of benzo[ ghi ]perylene were investigated. Abstract : Single crystals of three neutral charge-transfer complexes and a cation radical salt based on a C 2v -symmetric polycyclic aromatic hydrocarbon, benzo[ ghi ]perylene (bper), were obtained. The 1 : 1 complex with 7, 7, 8, 8-tetracyanoquinodimethane (TCNQ) involves DA-type alternating π-columns, whereas the alternating π-columns in the 2 : 1 TCNQ complex are flanked by another bper molecule. The in-plane rotation of bper in the 1 : 1 complex was significantly suppressed compared with that of coronene in (coronene) (TCNQ), which is associated with the lower molecular symmetry of bper. Whereas the 3 : 1 TCNQ complex involves DDA-type alternating π-columns flanked by another bper molecule, bper molecules in the 3 : 1 cation radical salt with Mo6 O19 2− have a columnar structure with a [101]-like charge-ordered pattern associated with intermolecular interactions in the bay region of bper. The dimerisation of charge-rich bper molecules results in an increased energy gap at the Fermi level, and consequently, semiconducting behaviour of the salt has a larger activation energy than that of the isostructural coronene salt in the partially charged state. The lower molecular symmetry of bper also affects the degeneracy of the frontier-orbitals; the energy difference between the HOMO and the HOMO−1 of bper is significantly larger than that of coronene, which is comparable to the intermolecular transfer integrals.